2021
DOI: 10.3389/fpubh.2021.622707
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Integrated Traditional Chinese and Western Medicine for Treating COVID-19: A Systematic Review and Meta-Analysis of RCTs

Abstract: Background: Integrated Chinese and Western medicine (integrated medicine) is routinely used in the treatment of coronavirus disease 2019 (COVID-19) in China. In this study, we undertook a systematic review and meta-analysis of published randomized controlled trials (RCTs) to evaluate the efficacy of integrated medicine therapy for patients with COVID-19.Methods: In this meta-analysis, we searched PubMed, Embase, Web of Science, SinoMed, China National Knowledge Infrastructure (CNKI), Chongqing VIP (CQVIP), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…As of October 20, 2021, the literature search yielded 674 results. After removing duplicates and excluding papers based on title and abstract screening, 21 SRs ( Ang et al, 2020 ; Du et al, 2021 ; Fan et al, 2020 ; Fan et al, 2021 ; Jiang et al, 2021 ; Li et al, 2021 ; Liang et al, 2021 ; Liu et al, 2021 ; Liu et al, 2020 ; Luo et al, 2021 ; Pang et al, 2020 ; Sun et al, 2020 ; Wang et al, 2021a ; Wang et al, 2021b ; Wu et al, 2021 ; Xiong et al, 2020 ; Yan et al, 2021 ; Yin et al, 2021 ; Zeng et al, 2020 ; Zhou et al, 2020 ; Zhuang et al, 2021 ) matching the inclusion criteria were identified ( Figure 1 ).
Figure 1 Study selection process.
…”
Section: Resultsmentioning
confidence: 99%
“…As of October 20, 2021, the literature search yielded 674 results. After removing duplicates and excluding papers based on title and abstract screening, 21 SRs ( Ang et al, 2020 ; Du et al, 2021 ; Fan et al, 2020 ; Fan et al, 2021 ; Jiang et al, 2021 ; Li et al, 2021 ; Liang et al, 2021 ; Liu et al, 2021 ; Liu et al, 2020 ; Luo et al, 2021 ; Pang et al, 2020 ; Sun et al, 2020 ; Wang et al, 2021a ; Wang et al, 2021b ; Wu et al, 2021 ; Xiong et al, 2020 ; Yan et al, 2021 ; Yin et al, 2021 ; Zeng et al, 2020 ; Zhou et al, 2020 ; Zhuang et al, 2021 ) matching the inclusion criteria were identified ( Figure 1 ).
Figure 1 Study selection process.
…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the argument has become political recently, making TCM an issue of political claims, which distorts what medicine should focus on and has hampered efforts to fight against COVID‐19 [ 38 ]. Despite this, there are many studies that have called for breaking down boundaries between Eastern and Western medicine and suggest that a proper combination of TCM and Western medicine could better control the disease progression and post‐disease syndromes [ 39 , 40 , 41 , 42 , 43 , 44 ]. Herein, as part of the efforts for probing these issues, TCM2COVID, a comprehensive database, documents the detailed information on anti‐COVID TCM treatments and is undoubtedly a useful toolkit to help settle the controversy surrounding the effects and mechanisms of TCM therapies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 21 systematic reviews have been identified that have similar findings to this current review ( Liu M. et al, 2020 ; Ang et al, 2020 ; Sun CY. et al, 2020 ; Xiong X. et al, 2020 ; Fan et al, 2020 ; Pang et al, 2020 ; Zeng et al, 2020 ; Zhou et al, 2020 ; Wang H. et al, 2021 ; Liu M. et al, 2021 ; Wang Q. et al, 2021 ; Du et al, 2021 ; Fan et al, 2021 ; Jiang et al, 2021 ; Li et al, 2021 ; Liang et al, 2021 ; Luo et al, 2021 ; Wu et al, 2021 ; Yan et al, 2021 ; Yin et al, 2021 ; Zhuang et al, 2021 ). The treatment of COVID-19 benefits from the rapid dissemination of evidence, providing data for the synthesizing of evidence disseminated was constantly complied by systematic reviewers, resulting in a large number of systematic reviews with overlapping evidence, each article updated with the inclusion of only one or two additional studies at the time of publication.…”
Section: Discussionmentioning
confidence: 99%